2015
DOI: 10.1111/all.12619
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis from adolescence to adulthood in the TOACS cohort: prevalence, persistence and comorbidities

Abstract: Persistence of atopic dermatitis in adulthood is common and affects quality of life. Persistent atopic dermatitis is particularly prevalent in those with early onset, allergic rhinitis and hand eczema in childhood. It is important to recognizing atopic dermatitis as a common and disabling disease not only in children but also in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 48 publications
(77 reference statements)
7
173
0
7
Order By: Relevance
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 91%
See 1 more Smart Citation
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 91%
“…After review of the titles and abstracts, 9326 were excluded; an additional 634 articles were excluded after full-text review. In total, 46 studies were included in the review, of which 44 had valid frequency data that could be pooled, 7 had valid data to assess the effects of gender, 6,23,28,31,44,45,48 6 for allergen sensitization, 6,17,23,36,40,45 and 3 for baseline AD severity 17,28,40 on disease persistence. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is presented in Fig 1. …”
Section: Literature Searchmentioning
confidence: 99%
“…In a recent study carried out in China, investigators reported that 77.5% of patients presented with AD after age 12 and suggested that late-onset AD is quite common [13]. Between 9% and 47% of cases of AD also appear de novo in adults (≥18 years), although the most widely accepted proportion is 9%-24.5% [2,5,15]. Among adults who develop AD, peak incidence occurs at age 20-40 years [20], although the disease does not completely subside after that.…”
Section: Epidemiologymentioning
confidence: 99%
“…The disease progresses with a chronic recurrent course before disappearing some time before puberty. However, it may persist into adulthood or present de novo during that period [1][2][3]. Bannister and Freeman [4] recently introduced the term adult-onset atopic dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Наше теперішнє розуміння про атопіч-ний дерматит (АД) різко змінилося на протязі останніх років, головним чином через значний про-грес у епідеміології та генетиці, величезний прорив в розумінні концепції атопічного маршу [1], а також розкриття нових аспектів щодо анамнезу хвороби [2,3] та вивчення форм АД, які персистують на протязі всього життя [4,5].…”
Section: C-159t поліморфізм гену Cd14 та цитокіновий профіль при атопunclassified